Plastic matrix composites with continuous fiber reinforcement (U.S. Dept. of Defense : [Distributed by DODSSP], 1991)
The properties of all basic plastics can be enhanced by the addition of fibers, whiskers, and particulate. Plastics so modified are referred to as organic or plastic matrix composites. The plastic matrix composites discussed in this handbook are restricted to those employing continuous fiber reinforcements. The fibers are fiberglass, carbon-graphite, aramid organic, and boron. Advantages in applications are discussed, and "pros and cons" are considered.
Title from title page of source document.
Also available in online version from Department of Defense Single Stock Point for Military Specifications, Standards and Related Publications (DODSSP).
Keywords: Fiber-reinforced plastics -- Handbooks, manuals, etc.; elektronické knihy; electronic books